2005
DOI: 10.1080/00222930500415195
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal Bryozoa (Cheilostomata) of Ketchikan, Alaska

Abstract: Assemblages of intertidal bryozoans are proving to be more species-rich than generally previously appreciated. This study found 31 species of cheilostome bryozoans at three rocky-intertidal sites at Ketchikan, Alaska, USA. Species richness varied considerably among the three collecting sites: 28 at East Tongass Narrows, 18 at Higgins Point, 10 at Settlers Cove. Each site had species not occurring at the other sites (12, two, and one species, respectively). The number of species per site was within the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(123 citation statements)
references
References 34 publications
5
118
0
Order By: Relevance
“…Although in the course of this study we directly observed embryos in only two of the species examined (C. spinifer and C. cryptoarmatus), internally brooded embryos have been reported for all the species examined (Dick and Ross, 1988;Dick et al, 2005;Grischenko et al, 2007). These data coupled with our observation of ooecia in the eight species studied strongly suggest that a reduced, maternally produced kenozooidal ooecium and internal brood sac are characters common to all species of Cauloramphus and should thus be appended as diagnostic characters for this genus.…”
Section: Evolution Of Internal Brooding In Calloporidaesupporting
confidence: 64%
See 4 more Smart Citations
“…Although in the course of this study we directly observed embryos in only two of the species examined (C. spinifer and C. cryptoarmatus), internally brooded embryos have been reported for all the species examined (Dick and Ross, 1988;Dick et al, 2005;Grischenko et al, 2007). These data coupled with our observation of ooecia in the eight species studied strongly suggest that a reduced, maternally produced kenozooidal ooecium and internal brood sac are characters common to all species of Cauloramphus and should thus be appended as diagnostic characters for this genus.…”
Section: Evolution Of Internal Brooding In Calloporidaesupporting
confidence: 64%
“…Hincks (1882, p. 250) indicated uncertainty in his original description of C. echinus by noting, "Ooecia (?)". Some species have been reported as having an inconspicuous, cap-like ovicell (e.g., Kluge, 1975;Mawatari and Mawatari, 1981;Dick and Ross, 1988). Despite previous reports of brood chambers in C. spinifer, Gostilovskaya (1978) noted for the White Sea population of this species that brood chambers were unknown.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations